Learning to teach culturally and linguistically diverse students through cross-cultural experiences. Issue 3 (4th May 2017) - Savva, Maria
Abstract: Teacher participation in cross-cultural experiences is often associated with the broadening of perspectives and increased intercultural sensitivity. While these qualities provide an overarching and important framework for intercultural development, they remain highly abstract. What exactly do we mean when we refer to these qualities? And in what ways, if any, do they translate into the classroom or school setting? Drawing on interviews from thirty Anglophone educators working in overseas international schools, this article focuses on links between broad-based changes in perspective and concrete changes in professional practice. Findings highlight an important relationship between personal and professional transformation, with the most noteworthy instructional changes emerging in the areas of language, communication style and religious/gender considerations. Most importantly, data from the study illustrate that the prolonged cross-cultural experience was not limited to changes in general disposition but had direct implications on the professional practice of participating educators.